In vitro models to study natural killer cell dynamics in the tumor microenvironment - Carannante, Valentina; Wiklund, Martin; Önfelt, Björn (Frontiers in Immunology, 2023)
Immunotherapy is revolutionizing the field of cancer therapy. The rapid development of new immunotherapeutic strategies is posing new challenges to the way we perform pre clinical studies, demanding novel in vitro methods to test treatments. Such methods should meet specific requirements, such as enabling the evaluation of immune cell cytotoxicity, cytokine release and infiltration using cancer models representative of the original disease. They should allow high-throughput and high-content analysis, to evaluate the efficacy of treatments, to understand the immune-evasion processes and develop new therapeutic targets. Ideally, they should be suitable for personalized immunotherapy testing, providing information for patient stratification. Consequently, the application of in vitro 3-dimensional (3D) cell culture models, such as tumor spheroids and organoids, is rapidly expanding in the immunotherapeutic field, coupled with the development of novel imaging based techniques and -omic analysis. In this paper, we review the recent advances in the development of in vitro 3D platforms suitable for natural killer (NK) cell-based cancer immunotherapy studies, highlighting the benefits and limitations of the current methods, and discuss new concepts and future directions of the field.